The Influence of Non-Performing Loan Policies, Loan to Deposit Ratio, and Operational Costs on Operating Income Against Financial Liabilities of PT. BPR Kawan Kepanjen Branch in Malang Regency - Godeliva Mida; Retno Ayu Dewi Novitawati; Fitria Setyaningrum (International Journal of Management and Business, 2026)
People’s Credit Banks (BPR) serve as a vital pillar of Indonesia’s financial system, supporting MSMEs and regional economic resilience through fund mobilization and credit distribution. However, limited capital and high exposure to credit, liquidity, operational, and compliance risks make liability stability a critical challenge. This study examines the influence of Non-Performing Loans (NPL), Loan to Deposit Ratio (LDR), and BOPO on the liabilities of PT BPR Kawan Kepanjen Malang to provide insights for strengthening risk management and financial stability. The method used is an associative quantitative with a causal-comparative design using secondary data from 2020–2024 financial statements totaling 32 observations. The analysis was conducted through descriptive statistics, classical assumption tests, and multiple linear regression with t-tests and F-tests. The results of the study indicate that Non-Performing Loans (NPL), Loan to Deposit Ratio (LDR), and BOPO each exert a significant influence on the liabilities of BPR Kawan Kepanjen. An increase in NPL re-flects a rise in problematic loans, thereby heightening funding needs and expanding lia-bilities. A high LDR indicates extensive loan distribution, which reduces liquidity and generates additional obligations. Similarly, a high BOPO signals low operational effi-ciency, leading to reduced profitability and greater reliance on external financing. Col-lectively, these three variables significantly affect liability stability, demonstrating that credit quality, liquidity, and operational efficiency jointly determine the extent of the bank’s obligations.